Immediate postoperative pain control with ropivacaine following laparoscopic-assisted vaginal hysterectomy: A randomized double-blind pilot study - Jae Young Kwack; Yong-Soon Kwon (Elsevier, 2018)
Objective: Although laparoscopic hysterectomy, a worldwide popular surgery, ensures faster recovery and less postoperative pain than with laparotomic hysterectomy, immediate pain control still improving postoperative care. We introduce an effective method, intraoperative injection of ropivacaine into both uterosacral ligaments, to control immediate postoperative pain. Materials and methods: We performed a prospective, double-blind, and randomized study. We analyzed 40 cases of laparoscopic vaginal hysterectomy performed between July 2015 and November 2016 by a single surgeon (Y.S.K.). We randomized the enrolled patients into the ropivacaine injection group and the saline injection group. Before the vaginal stump was closed, 7.5% ropivacaine or saline (10 mL) was administered into both uterosacral ligaments, 5 mL each. In all cases, the medicine was injected transvaginally before the vaginal stump was closed. The primary outcome was the postoperative pain intensity expressed by numeric ranking scale (NRS) scores at 2, 6, 12, and 24 h after injection. The secondary outcome was the amount of analgesics demanded for pain control during the 24 h after the surgery. Results: The pain intensity at 2 h after injection was significantly lower in the ropivacaine-injected group (p = .0234). There was no difference in pain intensity at 6, 12, and 24 h after injection and the amount of analgesics used. However, the total amount of opioid analgesic used was lower in the ropivacaine-injected group than in the placebo-injected group. (p = .0251). Conclusion: Intraoperative ropivacaine injection into both uterosacral ligaments during laparoscopic hysterectomy can reduce early postoperative pain and consumption of analgesics to improve postoperative care. Keywords: Laparoscopic hysterectomy, Ropivacaine, Postoperative pain, Uterosacral ligament